Progressive extreme heterotopic calcification. Issue 7 (17th May 2013) - Silengo, Margherita; Defilippi, Claudio; Belligni, Elga; Biamino, Elisa; Flex, Elisabetta; Brusco, Alfredo; Ferrero, Giovanni Battista; Tartaglia, Marco; Hennekam, Raoul C.
Abstract The formation of ectopic calcifications in soft tissues can occur either sporadically or as a genetically determined condition, and is seen only infrequently. We report on a girl in whom widespread, rapidly progressive ectopic calcifications were detected shortly after birth. Calcifications became present around all joints, tendons and ligaments, but did not involve internal organs and skin, and eventually caused almost complete immobility of the child at 2 years. There were no other health problems and cognitive development was normal. We compare the manifestations in the child to the characteristics of known entities causing ectopic calcifications and conclude the child differs to each. Laboratory evaluation failed to identify autoimmune phenomena as well as calcium metabolism or other biochemical abnormalities; molecular studies did not identify occurrence of mutations in disease genes known to be involved in ectopic calcifications. We conclude the manifestations in the child represent an unreported entity of hitherto unknown etiology. © 2013 Wiley Periodicals, Inc.